Interchange Teacher's edition - Richards, Jack C (Cambridge Universty Press, 2005)
Contiene : please call me beth. How do you spend your day. How much is it. Do you like rap. Tell me about your family. How often do you exercise. We had a great time. What's your neighborhood like. What does she look like. Have you ever ridden a camel.
Incluye bibliografía
Keywords: Language Taechers - Learning